2012
DOI: 10.1016/j.jdent.2012.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Restorative material and other tooth-specific variables associated with the decision to repair or replace defective restorations: Findings from The Dental PBRN

Abstract: Objectives Using data from dentists participating in The Dental Practice-Based Research Network (DPBRN), the study had 2 main objectives: (1) to identify and quantify the types of restorative materials in the existing failed restorations; and (2) to identify and quantify the materials used to repair or replace those failed restorations. Methods This cross-sectional study used a consecutive patient/restoration recruitment design. Practitioner-investigators recorded data on consecutive restorations in permanen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 45 publications
4
21
2
2
Order By: Relevance
“…Dental amalgam and composite resin were the most frequently used materials in this study 22,23 and the fact that most of the restorations were placed with composite resin confirms the worldwide trend of using composites as a universal restorative material (for anterior and posterior teeth). The growing desire of individuals for aesthetic materials also contributes to the increase in the use of composites 7,[24][25][26][27] .…”
Section: Discussionsupporting
confidence: 67%
“…Dental amalgam and composite resin were the most frequently used materials in this study 22,23 and the fact that most of the restorations were placed with composite resin confirms the worldwide trend of using composites as a universal restorative material (for anterior and posterior teeth). The growing desire of individuals for aesthetic materials also contributes to the increase in the use of composites 7,[24][25][26][27] .…”
Section: Discussionsupporting
confidence: 67%
“…The challenge for clinicians becomes that of deciding when intervention is required and what form this intervention should take. 23 The traditional approach to the management of restorations exhibiting signs of marginal deterioration (defective margins) or secondary caries as diagnosed clinically has been total restoration removal and replacement. This approach is based on the long-held premise that restorations with defective margins suffer damaging leakage and that lesions of caries formed at the margins of restorations adversely affect the tooth restoration interface down to and including the base of the cavity.…”
Section: Introductionmentioning
confidence: 99%
“…26 Following this trend, recent data from this cohort and from other studies have shown in the last decade an increase of both use and teaching of composite in comparison with amalgam. [27][28][29][30] In the present study, the overall failure rates for composite and amalgam were 9.36 and 12.20, respectively, and these differences were significant only in the bivariate analysis, losing the significance when multilevel analysis was performed.…”
Section: Variable/categorymentioning
confidence: 86%